Você está na página 1de 48

 

 

 

(M, +) M + M

(M, +) a, b, c M a + (b + c) = (a + b) + c id + M id + + m = m m + id + = m m M

(M, +) u M y M y + u = id + u + y = id + U (M ) M U (M ) = M (M, +) (M, +) a + b = b + a a, b M (M, +)

+ x M x

(M, +, ·) + · M

(M, +)

(M, ·)

a, b, c M a · (b + c) =

a · b + a · c

(a + b) · c = a · c + b · c

(M, ·) (M, ·) a · b = id + a = id + b = id + (M \ {0}, ·)

+ · 0 1

k N N k :=

{1, 2,

, k}

M S M S S

a, b M a b M ab M

A

=

n K

(K[x 1 , K

n A

n A A[x 1 ,

A [n] i=0

(α i1 ,

, x n ], +, ·) n

, x n ] =

α i

r

a i x α i

r

N

n

, α in ) x α i = j=1 x j α ij α ij N ∪ {0}

, x n ] a i A f x α i = 0 f M(f )

f

f

deg(f ) := max{deg(m) | m M(f )} deg(f ) = 1 f

A[x 1 ,

α

A[x 1 ,

f A [n] deg(f ) < 1 f A f

x n ]

f A[x 1 , a i · x α i a i

r

m M(f ) deg(m) = k=0

α k m

f

A[x 1 ,

,

, x n ]

, x n ] A

=

c i x i c i = a i + b i n m b m+1 = b m+2 = ··· = b n = 0

n m f · g = n+m c i x i c i = j+k=i a j b k

(A, +, ·)

max{n,m}

i=0

(A[x], +, ·) f + g

i=0

(A[x 1 ,

A[x 1 ,

, x n ], +, ·)

,

x n ] = A[x 1 ,

, x n1 ][x n ] n N n 2

n = 1

A[x 1 , x n A[x 1 ,

, x n1 ] , x n1 ]

∈ N n ≥ 2 n = 1 A [ x 1 , x n A

A[x 1 ,

f =

m

a

i x α i1

1

x

α

n

,

in

x n ] = A[x 1 ,

,

x n1 ][x n ] f A[x 1 ,

, a i A α ij N ∪ {0},

,

x n ]

i N m

A[x 1 ,

f = m

α

i=1 b i x n

in

j

i=1

N n

b i

= a i x α i1

1

x

α i n1

n1

A[x 1 ,

,

x n1 ]

, x n1 ][x n ]

(A, +, ·) A[x 1 ,

, x n ]

A[x 1 ,

n = 1 f = r

,

x n ] = A[x 1 ,

, x n1 ][x n ] n 2

=

= 0

i=0 a i x 1 i

1

0 g = r

2

i=0 b i x 1 i

= 0 r 1 , r 2 N a i , b i A a r 1 , b r 2

= 0 f · g

a r 1 b r 2

(A, +, ·) A[x 1 , A

= 0

b r 2 ( A, + , · ) A [ x 1 , A =

, x n ]

A A[x 1 ,

A[x 1 ,

f / A deg(f ) 1 g A[x 1 ] f · g = 1

A[x 1 ] deg(1) = deg(f ) + deg(g) 1 deg(f ) 1 deg(g) 0

, x n1 ]

, x n ] \ A

, x n1 ] , x n1 ] deg(1) 1

f

A f A[x 1 ,

deg(1) < 1 A[x 1 ,

, x n ] A

, x n ] n = 1 f A[x 1 ]

A[x 1 ,

,

x n ] \ A[x 1 ,

A[x 1 ,

A[x 1 ,

, x n ] A

[ x 1 , A [ x 1 , A [ x 1 , , x

(A, + 1 , · 1 ) (B, + 2 , · 2 ) ψ : A B a, b A ψ(a · 1 b) = ψ(a) · 2 ψ(b) ψ(a + 1 b) = ψ(a) + 2 ψ(b) ψ(1 A ) = 1 B Im(ψ) = {b B | ψ(a) = b a A} ψ Ker(ψ) = {a A | ψ(a) = 0} ψ ψ

A B ψ : A B Im(ψ) Ker(ψ) B A Ker(ψ) A

c, d Im(ψ) a, b A ψ(a) = c ψ(b) = d

cd = ψ(a)ψ(b) = ψ(ab) c d = ψ(a) ψ(b) = ψ(a b),

ab A a b A ψ(ab) = cd Im(ψ) ψ(a b) = a b Im(ψ) Im(ψ) B e, f Ker(ψ) ψ(e) = ψ(f ) = 0

ψ(e f ) = ψ(e) ψ(f ) = 0 ψ(ef ) = ψ(e)ψ(f ) = 0,

e f, ef Ker(ψ) Ker(ψ) A

a A b Ker(ψ) ψ(ab) = ψ(a)ψ(b) = ψ(a)0 = 0 ab Ker(ψ) Ker(ψ) Ker(ψ)

A

( ψ ) ψ ( ab ) = ψ ( a ) ψ ( b )

A I A

A I A/I = {a + I a A

| a A} a + I = {a + i | i I}

π : R R/I π(a) = a + I

a R I

A B ψ : A B A/Ker(ψ) Im(ψ)

R I R

ψ : A/Ker(ψ) Im(ψ) ψ(x + Ker(ψ)) = ψ(x) x A

ψ a + Ker(ψ) = b + Ker(ψ), a, b A a b Ker(ψ)

ψ(a b) = ψ(a) ψ(b) = 0

b Im(ψ) a A

ψ(a) = ψ(b) ψ(a + Ker(ψ)) = ψ(b + Ker(ψ))

a A ψ(a) = b b = ψ(a + Ker(ψ))

a b Ker(ψ)

ψ(a + Ker(ψ)) = ψ(b + Ker(ψ)) ψ(a) = ψ(b) a + Ker(ψ) = b + Ker(ψ)

( a ) = ψ ( b ) a + Ker ( ψ ) = b

K [n] K

M

=

a a, a M

a, b M a b b a a = b

a, b, c M a b b c a c

a b a b b a a = b a, b M

a b a b a, b, M

M

, x n ]

K[x 1 , M

M

a, b M a b a · c b · c, c M

M M

m, n M m = n

n

k

m LR n k N γ p = 0 k < p n γ k > 0

, x n ]

N γ p = 0 p < k γ k > 0

= j=0 x j β j m L n m n γ = β α

i=0 x i α i

n

f K[x 1 ,

f ml(f ) := max {m|m M(f )} f cl(f ) ml(f ) f tl(f ) := ml(f ) · cl(f )

p, q K[x 1 , p p|q t K[x 1 ,

x

t = x 1 c 1

=

t M

, x n ]

p q q

x n a n

q

, x n ] q = p · t

M

p

=

x 1 a 1

p, q

0

i

N n

p q

1 b 1

x n b n a i , b i

x n c n c i = b i a i 0 i N n

f, g K [n] g

f = q · g + r ml(g) ml(r)

= 0 q, r K [n]

ml(g) ml(f ) q = 0

r = f f

f 1 = f q 1 = tl(f 1 )/tl(g) f 2 = f 1 q 1 · g tl(f 1 ) f 2 ml(f 2 ) ml(f 1 ) (f n ) f i+1 = f i q i · g

q i = tl(f i )/tl(g) q i ml(g) | ml(f i )

f m f m = f m1 q m1 ·g ml(g) ml(f m ) f m1

= 0

r = q = 0 ml(g) | ml(f )

f i

f m = f m1 q m1 · g = f m2 q m2 · g q m1 · g

, f 2 f = f 1 = (q 1 +q 2 +···+q m1 )·g+f m

q = (q 1 + q 2 + ··· + q m1 ) r = f m f = q · g + r

f = q 2 · g + r 2 ml(g) ml(r 1 ) ml(g) ml(r 2 ) ml(g) ml(r 1 )

ml(g) m m M(r 1 ) r 2

(q 1 q 2 ) · g = r 2 r 1 r 2 = r 1 tl(g) | tl(r 2 r 1 ) M(r 2 r 1 ) M(r 1 ) M(r 2 ) r 2 = r 1 q 2 = q 1

r f g r g (f ) q f g

f 1 ,

a 1 , a 2 ,

ml(f i )

, f k K [n] f K [n]

f m2 , f m3 ,

q 1 , q 2 , r 1 , r 2 K [n] f

=

q 1 · g + r 1

q 1 · g + r 1 = q 2 · g + r 2

+ r 1 q 1 · g + r 1 = q 2 · g +

r K [n] f

, a k

= a 1 · f 1 +

+ a k · f k + r ml(r)

f K [n] a 1 , r 1 K [n]

f = f 1 · a 1 + r 1 tl(f 1 ) tl(r 1 ) a 2 , r 2 K [n]

r i f i m > 0 tl(f k ) tl(r m ) k N n f

r 1 = f 2 · a 2 + r 2 f = f 1 · a 1 + f 2 · a 2 + r 2

f = a 1 · f 1 + a 2 · f 2 + ··· + a k · f k + r m

r

f G = {f 1 ,

+ a k · f k + r m r f G = { f 1

, f k } r G (f)

f = xy 2 x, g 1 = xy y g 2 = y 2 x K[x, y] y x f g 1 g 2 f = yg 1 + g 2 g 2 g 1

f = xg 2 + 0.g 1 + x 2 x x 2 x

= 0

, x n ]

(A, +, ·) I A I A

K[x 1 ,